Finance, Trade, Man and Machines: A New-Ricardian Heckscher-Ohlin-Samuelson Model - Sugata Marjit; Gouranga Gopal Das (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper attempts to build up a Heckscher-Ohlin-Samuelson model of production and trade where capital is introduced outside the production process as a financial capital or credit as per the classical Ricardian wage fund framework. Stock of credit or financial capital as past savings, finances employment and machines or capital goods used in the process of production with Ricardian fixed coefficient technology. We derive the relationship between factor prices and rate of interest on one hand and relative price and endowments on the other. Availability of finance does not impact production or pattern of trade only nominal factor prices. International financial flows will not alter pattern of trade, but movement of labour and machines will. Such results change drastically when we consider a model with unemployment and finance dictates real outcomes much more than before. Introducing finance affects trade patterns with unemployment and especially with imperfect credit markets. The results could explain a vast array of stylized facts such as, financial crisis or shock, credit rationing and their impact on production, trade and unemployment. The paper has policy implications for role of financial development, quality of institutions in economic development.
Keywords: B12; B13; B17; F11; F63; F65; F16; O12; 330; wage-fund; Heckscher-Ohlin-Samuelson; Ricardo; inequality; credit; general equilibrium; financial development; unemployment; trade